Neuropathology of Congenital Heart Disease in an Inpatient Autopsy Cohort 2000–2017. Issue 7 (9th April 2020) - Rettenmaier, Leigh A.; Kirby, Patricia A.; Reinking, Benjamin E.; Viaene, Angela N.; Hefti, Marco M.
Abstract : Background: As a result of medical and surgical advancements in the management of congenital heart disease (CHD), survival rates have improved substantially, which has allowed the focus of CHD management to shift toward neurodevelopmental outcomes. Previous studies of the neuropathology occurring in CHD focused on cases preceding 1995 and reported high rates of white matter injury and intracranial hemorrhage, but do not reflect improvements in management of CHD in the past 2 decades. The purpose of this study is therefore to characterize the neuropathological lesions identified in subjects dying from CHD in a more‐recent cohort from 2 institutions. Methods and Results: We searched the autopsy archives at 2 major children's hospitals for patients with cyanotic congenital cardiac malformations who underwent autopsy. We identified 50 cases ranging in age from 20 gestational weeks to 46 years. Acquired neuropathological lesions were identified in 60% (30 of 50) of subjects upon postmortem examination. The most common lesions were intracranial hemorrhage, most commonly subarachnoid (12 of 50; 24%) or germinal matrix (10 of 50; 20%), hippocampal injuries (10 of 50; 20%), and diffuse white matter gliosis (8 of 50; 16%). Periventricular leukomalacia was rare (3 of 50). Twenty‐six subjects underwent repair or palliation of their lesions. Of the 50 subjects, 60% (30 of 50) had isolated CHD, whereas 24% (12 of 50) were diagnosed with chromosomal abnormalities (trisomy 13, 18, chromosomal deletions, and duplications) and 16% (8/50) had multiple congenital anomalies. Conclusions: In the modern era of pediatric cardiology and cardiac surgery, intracranial hemorrhage and microscopic gray matter hypoxic‐ischemic lesions are the dominant neuropathological lesions identified in patients coming to autopsy. Rates of more severe focal lesions, particularly periventricular leukomalacia, have decreased compared with historical controls.